2001
DOI: 10.1007/pl00000852
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in cell growth and cell death: molecular mechanisms and therapeutic applications

Abstract: Polyamines are aliphatic cations with multiple functions and are essential for life. Cellular polyamine levels are regulated by multiple pathways such as synthesis from amino acid precursors, cellular uptake mechanisms that salvage polyamines from diet and intestinal microorganisms, as well as stepwise degradation and efflux. Investigations using polyamine biosynthetic inhibitors indicate that alterations in cellular polyamine levels modulate normal and cancer cell growth. Studies using transgenic mice overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
582
0
9

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(606 citation statements)
references
References 121 publications
(199 reference statements)
15
582
0
9
Order By: Relevance
“…Polyamines are intracellular polycationic molecules found in all living cells (Pegg and McCann, 1982;Tabor and Tabor, 1984;Thomas and Thomas, 2001). Polyamine levels are highly regulated by biosynthetic and metabolizing enzymes, and an elevated cellular polyamine concentration has been linked to the initiation and progression of cancer (Hibshoosh et al, 1991;O'Brien et al, 1992;Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are intracellular polycationic molecules found in all living cells (Pegg and McCann, 1982;Tabor and Tabor, 1984;Thomas and Thomas, 2001). Polyamine levels are highly regulated by biosynthetic and metabolizing enzymes, and an elevated cellular polyamine concentration has been linked to the initiation and progression of cancer (Hibshoosh et al, 1991;O'Brien et al, 1992;Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The condensation of stiff, highly charged DNA molecules into compact structures by condensing agents ranging from multivalent ions 1 to small cationic proteins 2,3 is of major biological and therapeutic importance 4,5 , yet the underlying microscopic mechanism remains poorly understood 1,6-9 . It has been proposed 7,10 that DNA condensation is a purely electrostatic phenomenon driven by the existence of a strongly correlated liquid (SCL) of counterions at the DNA surface.…”
mentioning
confidence: 99%
“…Studies in mammalian cells showed direct binding of PAs to nucleic acids and ability to modulate their conformation and interaction with proteins, playing a role in cellular signaling. 4 At different phases of mitosis in Scots pine related to the expression of morphogenic capacity of the tissue in culture and protection against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…1 They have been implicated in a wide range of biological processes, including cell growth and division, stabilization of nucleic acids and membranes, protein synthesis and chromatin function, and biotic and abiotic stresses responses. [2][3][4][5] The most common PAs are spermidine and spermine, together with their diamine precursor putrescine. The biosynthesis of PAs is controlled in plants primarily by three enzymes: arginine decarboxylase (ADC; EC 4.1.…”
Section: Introductionmentioning
confidence: 99%